Some fractional integrals inequalities for h-preinvex functions and applications to numerical integration - Sun, Wenbing; Xie, Wenping (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
An identity with parameters is constructed via Riemann-Liouville fractional integrals. With that, we derive some fractional integrals inequalities with parameters for h-preinvex functions. The "midpoint type", "trapezoidal type" and "Simpson type" integral inequalities are obtained respectively when the parameters are given special values. Finally,the error estimates of numerical integration are proposed to illustrate the applications of the results.